AKR1B10 as a Potential Novel Serum Biomarker for Breast Cancer: A Pilot Study - Cao, Zhe; Delfino, Kristin; Tiwari, Vivek; Wang, Xin; Hannan, Abdul; Zaidi, Fawwad; McClintock, Andrew; Robinson, Kathy; Zhu, Yun; Gao, John; Cao, Deliang; Rao, Krishna (Frontiers in Oncology, 2022)
Background Aldo-keto reductase 1B10 (AKR1B10) is a secretory protein that is upregulated in breast cancer. Objective This case-controlled pilot study evaluated the serum level of AKR1B10 in healthy women and patients with a localized or metastatic breast cancer. Methods AKR1B10 levels were measured by ELISA and IHC in several patient cohorts. Results Our data showed that serum AKR1B10 was significantly elevated in patients with localized (6.72 ± 0.92 ng/ml) or metastatic (7.79 ± 1.13 ng/ml) disease compared to cancer-free healthy women (1.69 ± 0.17 ng/ml) (p<0.001); the serum AKR1B10 was correlated with its expression in tumor tissues, but not with the tumor burden, molecular subtypes or histological stages. After surgical removal of primary tumors, the serum AKR1B10 was rapidly decreased within 3 days and plateaued at a level similar to that of healthy controls in most patients. ROC curve analysis suggested the optimal diagnostic cut-off value of serum AKR1B10 at 3.456 ng/ml with AUC 0.9045 ± 0.0337 (95% CI 0.8384 – 0.9706), sensitivity 84.75% (95% CI 73.01% to 92.78%), and specificity 93.88% (95% CI 83.13% to 98.72%). Conclusions These data indicate the potential value of serum AKR1B10 as a biomarker of breast cancer.